2016
DOI: 10.4103/1735-5362.194868
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic improvement in dissolution rate of albendazole by a simple, one-step, industrially scalable technique

Abstract: Low solubility and dissolution rate are the primary challenges in the drug development which substantially impact the oral absorption and bioavailability of drugs. Due to the poor water solubility, Albendazole (ABZ) is poorly absorbed from the gastrointestinal tract and shows low oral bioavailability (5%) which is a major disadvantage for the systemic use of ABZ. To improve the solubility and dissolution rate of ABZ, different classes of hydrophilic excipients such as sugars (lactose, sucrose, and glucose), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Finally, the third parameter of potential discriminating power is simply LogP in variant computations protocols. This is in accord with chemical intuition and pharmaceutical drug delivery strategies (Brough et al, 2015;Ghanbarzadeh et al, 2016;Kalepu and Nekkanti, 2015;Maggi et al, 2013;Sareen et al, 2012;Savjani et al, 2012;Serajuddin, 1999;Sruti et al, 2013) that differences in polarities between drug and excipient is a main driving force toward dissolution. Many examples of such cases can be found in the literature, including cocrystals but also other types of solid mixtures such as inclusion complexes with cyclodextrins (Dua et al, 2011;M Badr-Eldin et al, 2013;Thiry et al, 2017aThiry et al, , 2017b and dispersions with soluble polymers (Brough et al, 2015;Choi and Park, 2017;Ibrahim et al, 2010;Maggi et al, 2013;Six et al, 2004;Thiry et al, 2017a).…”
Section: Selection Of Appropriate Molecular Descriptorsupporting
confidence: 73%
“…Finally, the third parameter of potential discriminating power is simply LogP in variant computations protocols. This is in accord with chemical intuition and pharmaceutical drug delivery strategies (Brough et al, 2015;Ghanbarzadeh et al, 2016;Kalepu and Nekkanti, 2015;Maggi et al, 2013;Sareen et al, 2012;Savjani et al, 2012;Serajuddin, 1999;Sruti et al, 2013) that differences in polarities between drug and excipient is a main driving force toward dissolution. Many examples of such cases can be found in the literature, including cocrystals but also other types of solid mixtures such as inclusion complexes with cyclodextrins (Dua et al, 2011;M Badr-Eldin et al, 2013;Thiry et al, 2017aThiry et al, , 2017b and dispersions with soluble polymers (Brough et al, 2015;Choi and Park, 2017;Ibrahim et al, 2010;Maggi et al, 2013;Six et al, 2004;Thiry et al, 2017a).…”
Section: Selection Of Appropriate Molecular Descriptorsupporting
confidence: 73%
“…Taraschewski et al (1990) reported that levamisole presented efficacy against N. rutili and E. truttae after 1 hr of exposure. No concentration of albendazole, fenbendazole, mebendazole or loperamide showed in vitro efficacy against N. buttnerae of C. macropomum, since they are poorly soluble in water, resulting therefore in variable and incomplete bioavailability (Ghanbarzadeh et al, 2016;Ibrahim & Al-Anazi, 2013;Pacheco et al, 2018;Romero, Navarro, Sanchez, & Valero, 2014;Taraschewski et al, 1990). Similar inefficacy of albendazole, fenbendazole and mebendazole has also been reported in relation to species of acanthocephalans, nematodes, monogeneans and trematodes parasitizing different fish species (Reimschuessel, Gieseker, & Poynton, 2011;Romero et al, 2014;Taraschewski et al, 1990;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…The observed melting behaviour indicates that the drug is in a crystalline state rather than an amorphous state. The other excipients like PL 90G, Cap MCM C10, Cr A25 and SDC exhibited respective endothermic peaks at 62.32 °C, 29.97 °C, 55.84 °C and 74.55 °C corresponding to their reported melting point 40 , 65 67 . Likewise, the developed DE formulation displayed an endothermic peak at 99.89 °C and the disappearance of drug peak may be ascribed to the encapsulation of drug in the interiors of the developed system.…”
Section: Resultsmentioning
confidence: 99%